"DISSECTING" QUARTZITE AND BASALT BIPOLAR FLAKE SHAPE: A MORPHOMETRIC COMPARISON OF EXPERIMENTAL REPLICATIONS FROM OLDUVAI GORGE, TANZANIA. (November 2015) - Gurtov, Alia N.; Buchanan, Briggs; Eren, Metin I.
Abstract : In this pilot study we explore the relationship between bipolar flake shape and stone raw material differences. We conducted a morphometric analysis of 40 quartzite and 40 basalt experimentally replicated specimens from Olduvai Gorge, Tanzania. We carried out two sets of statistical analyses to investigate the shapes of quartzite and basalt bipolar flakes. Our first set of analyses focused on statistical comparisons of five morphometric variables recorded on the two samples of bipolar flakes. For the second set of analyses we used principal components analysis (PCA) to investigate shape differences among the quartzite and basalt bipolar flakes. Our results suggested that there are no significant differences amongst the quartzite and basalt samples. These results are consistent with the hypothesis that the close association between quartzite and bipolar reduction during the Lower Paleolithic at Olduvai Gorge is due to a single motivating factor, namely, expediency. However, we emphasize that more experiments altering test parameters and variables are needed, as are direct quantitative comparisons between experimental and archaeological datasets. Future experiments may uncover additional motivating factors for the prominent quartzite-bipolar reduction found at Olduvai Gorge.